2012
DOI: 10.1136/gutjnl-2012-302344
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12supplementation improves rates of sustained viral response in patients chronically infected with hepatitis C virus

Abstract: Vitamin B12 supplementation significantly improves SVR rates in HCV-infected patients naïve to antiviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 22 publications
(17 reference statements)
2
23
1
1
Order By: Relevance
“…The results of IL-28B genotyping in our patients did not show any significant differences in the distribution of IL-28B genotypes (C/C, C/T and T/T) between two treatment groups, indicating that the higher rate of SVR observed in SOC + B12 patients was not affected by IL-28B genotype. Our findings were in agreement with the open-label pilot study by Rocco et al 25 , which reported that the addition of vitamin B12 to SOC significantly improved the rate of virological response in patients with chronic HCV infection. Accordingly, Rosenberg and Hagen 32 , in their work showed that high levels of vitamin B12 in serum is favorable for achieving an ETVR in CHC patients treated with SOC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of IL-28B genotyping in our patients did not show any significant differences in the distribution of IL-28B genotypes (C/C, C/T and T/T) between two treatment groups, indicating that the higher rate of SVR observed in SOC + B12 patients was not affected by IL-28B genotype. Our findings were in agreement with the open-label pilot study by Rocco et al 25 , which reported that the addition of vitamin B12 to SOC significantly improved the rate of virological response in patients with chronic HCV infection. Accordingly, Rosenberg and Hagen 32 , in their work showed that high levels of vitamin B12 in serum is favorable for achieving an ETVR in CHC patients treated with SOC.…”
Section: Discussionsupporting
confidence: 93%
“…Since then, several studies have reported the correlation between vitamin B12 and virological response of chronic hepatitis C infection receiving SOC 25,32,33 . Considering these evidences, the aim of the current study was to evaluate the possible effects of adding vitamin B12 by injection (at a dose of 5000 microgram) to PegIFN and RBV combination therapy on the virological response in treatment-naive patients with chronic HCV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivitamin supplementation (including vitamins B, C, and E) has been shown to be beneficial for patients with human immunodeficiency virus (HIV) 68 and tuberculosis. 69,70 Vitamin B 12 has been shown to decrease viral replication and increase sustained viral response rates in patients of hepatitis C. 71 Similarly, vitamin C supplementation has been shown to be beneficial against respiratory tract infections and pneumonia, 72 whereas selenium supplementation has been shown to reduce parasitemia and the induced organ damage in parasitic infections, such as Trypanosoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to antiviral agents described above, vitamin B12 was also reported to act as an inhibitor of HCV replication. The use of vitamin B12 with SOC drugs raised the SVR rate to the level higher than the rate noted in patients treated with SOC alone [35] . Recently, it has been observed that vitamin D also acts against HCV in vitro.…”
Section: Other Antiviral Agentsmentioning
confidence: 81%